3 - Exploring Local Conceptions of Poverty, Wealth and Well-Being: Field Evidence from Mashonaland West Province of Zimbabwe - Mtapuri, Oliver (Africa Development, 2021)
This article presents the conceptions of poverty by the poor in Mashonaland West Province of Zimbabwe. It seeks to broaden the discussion of poverty around the definition of the poor from the perspective of the poor. A cause-effect frame- work for poverty analysis is proposed, as well as the introduction of the notion of ‘enclavity’ within a family in poverty discourse. These are the two primary contri- butions of this paper. The research suggests that, due to deepening poverty, people create enclaves around husband/wife relationships as a new form of resil- ience/collectivity. While the poor suffer from a lack of assets, ethics and networks breakdown as a result of poverty. The results suggest, as elsewhere, that poverty is multifaceted, thus driving to some confluence of conception.